The Effect of Physical Ergonomics Training on Sleep Quality and Musculoskeletal System Problems in Factory Workers - Sibel Kutlu Özkan; Oğuzhan Bahadır Demir (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: This study aimed to assess the impact of physical ergonomics training on sleep quality and musculoskeletal issues among factory workers.Method: Twenty-five factory employees aged 18-60, without neurological or emotional issues, participated. Data collection at baseline included a demographic form, the Pittsburgh Sleep Quality Index (PSQI), and the Cornell Musculoskeletal Discomfort Questionnaire. Following physical ergonomics training, these assessments were repeated after four weeks. Continuous data were analyzed using SPSS 29.0, with distribution differences tested by Kruskal-Wallis and Shapiro-Wilk methods. The Wilcoxon method determined any significant changes in non-normally distributed variables between initial and final measures.Results: A significant improvement in PSQI scores (p=0.002) indicated enhanced sleep quality post-intervention. In the Cornell Musculoskeletal Discomfort data, a statistically significant reduction in neck pain was noted following training, while reductions in shoulder, back, and lumbar pain levels were not statistically significant. Although average score changes in the hip, upper and lower legs, knees, and feet suggested a trend in improvement, these differences were not statistically significant.Conclusion: The findings suggest that physical ergonomics training could improve sleep quality and potentially reduce musculoskeletal discomfort among factory workers, highlighting its value for workplace health interventions.